Mrs. Fletcher : a novel - Perrotta, Tom, 1961- (New York : Scribner, 2017)
"From one of the most popular and bestselling authors of our time, a penetrating and hilarious new novel about sex, love, and identity on the frontlines of America's culture wars. Eve Fletcher is trying to figure out what comes next. A forty-six-year-old divorcee whose beloved only child has just left for college, Eve is struggling to adjust to her empty nest when one night her phone lights up with a text message. Sent from an anonymous number, the mysterious sender tells Eve, "U R my MILF!" Over the months that follow, that message comes to obsess Eve. While leading her all-too-placid life--serving as Executive Director of the local senior center by day and taking a community college course on Gender and Society at night--Eve can't curtail her own interest in a porn website called MILFateria.com, which features the erotic exploits of ordinary, middle-aged women like herself. Before long, Eve's online fixations begin to spill over into real life, revealing new romantic possibilities that threaten to upend her quiet suburban existence. Meanwhile, miles away at the state college, Eve's son Brendan--a jock and aspiring frat boy--discovers that his new campus isn't nearly as welcoming to his hard-partying lifestyle as he had imagined. Only a few weeks into his freshman year, Brendan is floundering in a college environment that challenges his white-dude privilege and shames him for his outmoded, chauvinistic ideas of sex. As the New England autumn turns cold, both mother and son find themselves enmeshed in morally fraught situations that come to a head on one fateful November night. Sharp, witty, and provocative, Mrs. Fletcher is a timeless examination of sexuality, identity, parenthood, and the big clarifying mistakes people can make when they're no longer sure of who they are or where they belong"--
Keywords: Middle-aged women -- Fiction; Mothers and sons -- Fiction; College students -- Fiction; FICTION / Literary; FICTION / Family Life; FICTION / Coming of Age; Domestic fiction; Humorous fiction